A discussion of gender, ethnicity, and intersectionality, at the Serb Business Association forum - Paravina, Aleksandra (Frontiers in Sociology, 2024)
Qualitative transdisciplinary research has contributed to the development of a dynamic scientific area that is best suited to analyze real-life data from real people. To determine how ethnicity and gender intersect to shape the social worlds of the participants in a Serb business discussion forum, I apply two theoretical orientations based on ethnomethodology: Conversation Analysis (CA) and membership categorization analysis (MCA). I analyze 15 videos with predominantly female Serb discussants. My findings from this project reveal a significant presence of stigma in the perceptions of Serb ethnicity in Croatia. I argue that due to patriarchal values as a type of cultural cache, Serb women experience demeaning gender categories in various areas of their lives. To improve this situation, it is suggested that there is a need for feminist ethics of care and a coalition with men.